Use a Spoon as a Spade?: Changes in the Upper and Lower Alpha Bands in Evaluating Alternate Object Use - Rataj, Karolina; Nazareth, Deniece S.; van der Velde, Frank (Frontiers in Psychology, 2018)
Previous electrophysiological research on human creative cognition has related creative ideation to increased activity in the alpha band, an effect which mainly reflects increased general attentional demands. Research on alpha unrelated to creativity has revealed different functional roles of the upper (semantic processes) and lower (attentional processes) alpha sub-bands. At the same time, the need to dissect creative thinking into specific cognitive operations, such as, semantic processing, re-representation, or conceptual expansion has become evident. The main aim of the reported study was to test whether increased semantic processing demands linked to creating conceptual re-representations of objects required for evaluating alternate uses modulate activity in the upper and/or lower alpha sub-bands. For this purpose, we performed an alternate use evaluation task (AUeT), in which participants saw word pairs representing common uses, alternate uses, and unrelated word pairs, and evaluated whether a given use was common or uncommon (question 1), and how usable it was (question 2). Such an approach allowed us to examine the time-course of semantic processing involved in evaluating alternate uses. Additionally, the results could be contrasted with event-related potential (ERP) studies on creative language and semantic processing. We assumed that demands related to access and integration of semantic information needed to create a re-representation of objects (alternate uses) would be larger than in the case of common uses, which do not require creating a re-representation. This should be reflected in more activity in the alpha band in response to alternate than common uses, which was observed in the analysis of the upper alpha band over parieto-occipital sites. In the lower alpha band, more activity over the left than right anterior sites was observed for alternate uses, which might reflect increased attentional demands. Additionally, in the ERP analysis, alternate uses evoked larger N400 (400 - 500 ms) amplitudes than common uses, a pattern that extended to later time windows (500 - 1,000 ms). Overall, the results indicate increased semantic processing demands in alternate use evaluation, possibly linked to the creation of conceptual re-representations.